Evaluation of UNILORIN Dam Moulding Sand Properties for Foundry Applications - Yusuf L. SHUAIB-BABATA; Kabiru S. AJAO; Yusuf O. BUSARI; Ibrahim O. AMBALI; Kehinde O. ARUNA; Henrietta O. COKER; Toheeb A. NURUDEEN (FUDMA Journal of Engineering and Technology, 2026)
The availability of suitable and cost-effective moulding sand within Nigeria is a critical requirement in foundry operations, as sand properties significantly influence casting quality, dimensional accuracy and surface finish. Evaluation of moulding sands properties in Nigeria is key in determining their usefulness for foundry practices. In developing countries, foundries often depend on imported sand due to uncertainty about local materials, with rise in production costs and hindering local industry sustainability. The University of Ilorin Dam may provide a viable source of sand for foundry moulding, but there is insufficient scientific data on its crucial engineering properties that is needed to assess its suitability for metal casting. In this research, the chemical and physico-mechanical properties of Unilorin dam natural moulding sand were evaluated to determine its suitability for foundry operations using America Foundrymen’s Society standards. The experimental results showed that the sand belong to Alumino-silicate group containing silica (58.621%) and alumina (14.074%), with smaller proportions of other alkali elements such as sodium dioxide, potassium dioxide, lime, iron oxide, magnesia and titanium dioxide. The sand exhibited clay content (4.98%), moisture content (0.68%), grain fineness number (63.91), green compressive strength (87.29 KN/m²), dry compressive strength (234.02 KN/m²), specific gravity (2.56), shatter Index (73.03%), bulk density (2306.46 kg/m3), permeability (0.005330 cm/sec) and refractoriness (>510°C). Most of these results were within the AFS standard recommendation values for non-ferrous metal casting. Hence, Unilorin dam natural moulding sand was found suitable as moulding sand for various types of casting of metals like light grey iron, aluminum, bronze, brass. The sand is also suitable for manufacturing of ceramics, refractory products, or possibly as a raw material for pozzolanic materials. Effective utilization of this sand for foundry applications will help to boost the economy of the Nation and subsequently aid in reducing the problem of unemployment.
Keywords: Foundry, Casting, Unilorin dam sand, Chemical Analysis, Physico-mechanical properties.